Phosphorus adsorption behaviors of MgO modified biochars derived from waste woody biomass resources. Issue 2 (April 2020) - Oginni, Oluwatosin; Yakaboylu, Gunes A.; Singh, Kaushlendra; Sabolsky, Edward M.; Unal-Tosun, Gulcin; Jaisi, Deb; Khanal, Samir; Shah, Ajay
Highlights: The pH values of all the biochars showed they are alkaline in nature. MgO modified biochars had higher biochar yield due to MgO enrichment. Cation exchange capacities of the MgO modified biochars significantly increased. MgO modified biochars exhibited higher phosphorus adsorption capacities. Abstract: This study investigated the phosphorus adsorption behaviors of pristine and MgO modified biochars produced from woody biomass precursors (having different anatomical characteristics and similar specific gravities) and their MgCl2 impregnated counterparts. The biomass precursors were Longleaf pine wood shavings, Red Oak and Hard Maple sawdusts. The microstructural, physico-chemical, textural, and phosphorus adsorption characteristics of the pristine and MgO modified biochars were examined. The percent yields (45.01 – 56.35%) of the MgO modified biochars were higher than the percent yields (29.29 – 30.08%) of the pristine biochars, mainly due to the presence of added MgO. The pH of all the biochars showed that they were alkaline in nature. The cation exchange capacities of the pristine and MgO modified biochars were 1.62 – 3.20 cmol/kg and 84.81 – 111.12 cmol/kg, respectively. The specific surface areas of the pristine and MgO modified biochars were 0.26 - 8.82 m 2 /g and 22.02 - 28.07 m 2 /g, respectively. The phosphorus adsorption capacities of the pristine and MgO modified biochars were 1.88 – 2.78 mg/g and 28.20 – 29.22 mg/g, respectively. The pristine hardwood derived biochars (Hard Maple and Red Oak) showed better phosphorous adsorption capacities than the pristine softwood derived biochar (Longleaf Pine), and the MgO modified biochars showed 11 times higher phosphorus adsorption capacities than the pristine biochars.